Kontrol Diri Dan Kecemasan Siswa Sma Dalam Menghadapi Ujian Nasional - Anggarawati, Desy, Siti Nurina Hakim, S.Psi, M.Si, Psi (2017)
National exam (UN) as one of the stage to measure the achievement of national graduate student competency standards at high school level. Often referred to as a source of students' anxiety. In this case, it is necessary to take an action to overcome the anxiety experienced by the high school students in facing the national exams with self control. Anxiety due tue national exam is influenced by several factors, such as self-control. The purpose of this study was to determine the relationship between self-control with the anxiety of high school students in facing the national exams. The proposed hypothesis is that there is a negative relationship between self-control and anxiety of high school students in the face of national examination. This study applied correlation method. Subjects used in this study were high school students, with the total population of 109 students of grade XII (L = 30, P = 79) at the age between 15-18 years old, high school teens who sit grade III and the samples were taken by using purposive sampling technique. The instrument used to obtain the data was self-control scale (SCS) and anxiety scale (AS). Then, the data were analyzed by using non-parametric analysis because the data distribution anxiety does not meet the normal distribution with SPSS (Statistical Product and Service Solution) 15.0 for Windows program. Based on the result of analysis, obtained rvalue - 0.075; (p) = 0.218 (p > 0.05) means that there is no correlation between self-control with the anxiety of students in facing the national exams. Variable Mean anxiety have The Empirical Mean (EM) of anxiety variable = 71.17 and the Hypothetical Mean (HM) = 70, meaning that the anxiety is moderate and the Empirical Mean (EM) of self-control variable = 66.31 and the Hypothetical Mean (HM) = 52.5, meaning that the level of self-control is high. The effective contribution of self-control variable to anxiety is 5.625%, and therefore 94.375% of remaining are other factors that influence anxiety.